2017
DOI: 10.1038/cddis.2017.209
|View full text |Cite
|
Sign up to set email alerts
|

Survivin, a key player in cancer progression, increases in obesity and protects adipose tissue stem cells from apoptosis

Abstract: Adipose tissue (AT) has a central role in obesity-related metabolic imbalance through the dysregulated production of cytokines and adipokines. In addition to its known risk for cardiovascular disease and diabetes, obesity is also a major risk for cancer. We investigated the impact of obesity for the expression of survivin, an antiapoptotic protein upregulated by adipokines and a diagnostic biomarker of tumor onset and recurrence. In a cross-sectional study of 111 subjects classified by body mass index, circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 65 publications
(71 reference statements)
1
18
1
Order By: Relevance
“…Moreover, it has been demonstrated that a pro-inflammatory stimulus such as tumor necrosis factor α (TNF-α) can stimulate the proliferation of adipocyte precursors ( Zubkova et al., 2016 ). Accordingly, precursors may be conditioned by the systemic inflammatory environment characteristic of CD, as previously described in other inflammatory-based diseases, including obesity, whereby an activation of the ASC niche occurs through an increase in ASC proliferative capacities ( Pachon-Pena et al., 2016 , Serena et al., 2016 ) and a decrease in their sensitivity to apoptosis ( Ejarque et al., 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, it has been demonstrated that a pro-inflammatory stimulus such as tumor necrosis factor α (TNF-α) can stimulate the proliferation of adipocyte precursors ( Zubkova et al., 2016 ). Accordingly, precursors may be conditioned by the systemic inflammatory environment characteristic of CD, as previously described in other inflammatory-based diseases, including obesity, whereby an activation of the ASC niche occurs through an increase in ASC proliferative capacities ( Pachon-Pena et al., 2016 , Serena et al., 2016 ) and a decrease in their sensitivity to apoptosis ( Ejarque et al., 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…Survivin is an antiapoptotic protein strongly linked to cancer cell growth. Consistently, its increase in obesity protects MSCs from apoptosis and controls adipocyte lipolysis and lipid storage and may contribute to cancer progression (77,78). Increased lipid content and external lipid stimuli largely modify adipocyte-BC cell communication.…”
Section: Adipose Cells As Link Between Metabolic Derangements and Bcmentioning
confidence: 95%
“…CD44 + /CD105 + human amniotic fluid MSCs, that proliferate rapidly and are ideal for stem cell transplantation, also express high levels of survivin [ 39 ]. The involvement of hematopoietic adipocyte-derived stem cells (ASCs) in apoptotic resistance displayed by adipocyte tissue in obese subjects was correlated to upregulated survivin expression [ 40 ]. Keratinocyte Stem Cells (KSCs) show high expression of survivin, that plays a prominent role in preventing abnormal mitosis in these cells [ 41 , 42 ].…”
Section: Survivin In Stem Cellsmentioning
confidence: 99%